KONSTITUSIONALITAS PENGHAYAT ALIRAN KEPERCAYAAN DALAM SISTEM HUKUM NASIONAL DAN HUKUM ISLAM - Riesky Milly Valdo; Afdil Azizi (Institut Agama Islam Negeri Batusangkar, 2020)
The main problem in this thesis is where the writer wants to see how the constitutionality of Beliefs in Indonesia is in the national legal system and Islamic law, which in national law has been explained a lot in the legal umbrella starting from the 1945 Constitution to the Decree. The minister and most recently are related to the Constitutional Court Decision Number 97 / PUU-XIV / 2016. The author also wants to see how the views of Islamic law on followers of this belief.Keyword:konstitusionalitas, hukumnasional, hukum Islam